Platelet Phenotype and Function in the Setting of Pediatric Extracorporeal Membrane Oxygenation (ECMO): A Systematic Review - Yaw, Hui Ping; Van Den Helm, Suelyn; MacLaren, Graeme; Linden, Matthew; Monagle, Paul; Ignjatovic, Vera (Frontiers in Cardiovascular Medicine, 2019)
Background: Despite increasing technical improvement and extracorporeal membrane oxygenation (ECMO)-related knowledge over the past three decades, morbidity and mortality associated with bleeding and clotting complications remain high in pediatric patients undergoing ECMO. Platelets, a key element of the coagulation system, have been proposed to be the main cause of coagulopathy in the setting of ECMO. This systematic review aims to summarize and discuss the existing knowledge of platelet phenotype and function in the pediatric ECMO population. Methods: A systematic review was conducted for the Embase, Medline, and PubMed databases following the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. Results: The detailed study selection process yielded a total of 765 studies and only 3 studies that fulfilled the selection criteria were included in this review. Techniques used to assess platelet function in the three existing studies included platelet aggregometry, flow cytometry, and thromboelastography-platelet mapping. The finding that is common to the three studies is reduced platelet function in pediatric patients during ECMO either compared to before the initiation of ECMO or in non-survivors compared to survivors. Two studies demonstrated reduced platelet aggregation that are irreversible by platelet transfusion during ECMO. Two studies reported bleeding events and mortality in children on ECMO and none of the studies investigated thrombotic events. Conclusions: This systematic review demonstrates the extremely limited information available for platelet phenotype and function in the pediatric ECMO population. Evidence from the existing literature suggests reduced platelet aggregation and increased platelet activation in children during ECMO. However, this needs to be interpreted with care due to the limitations associated with the techniques used for platelet function testing. Furthermore, the association between platelet dysfunction and clinical outcomes in the pediatric ECMO population remains elusive. Multiple research gaps have been identified when it comes to the knowledge of platelet phenotype and function of children on ECMO, highlighting the need for robust, well-designed studies in this setting.